2012
DOI: 10.1088/0957-4484/23/27/275103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytotoxicity of gold–doxorubicin and InP–doxorubicin conjugates

Abstract: Direct comparisons of different types of nanoparticles for drug delivery have seldom been performed. In this study we compare the physical properties and cellular activity of doxorubicin (Dox) conjugates to gold nanoparticles (Au) and InP quantum dots of comparable diameter. Although the Au particles alone are non-toxic and InP is moderately toxic, Au-Dox is more effective than InP-Dox against the Dox-resistant B16 melanoma cell line. Light exposure does not augment the efficacy of InP-Dox, suggesting that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Chemoresistance is mainly due to over expression of a membrane transporter, p-glycoprotein (pgp) that actively pumps DOX out of the cell [33]. DOX conjugated nanoparticle based drug delivery system evades this mode of efflux as it is taken up by the cells efficiently through endocytosis [34,35]. Colloidal AuNPs incorporating anticancer agents can overcome resistance to drug action, thus reducing the need for higher doses and therefore reducing their ill effects towards normal cells [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoresistance is mainly due to over expression of a membrane transporter, p-glycoprotein (pgp) that actively pumps DOX out of the cell [33]. DOX conjugated nanoparticle based drug delivery system evades this mode of efflux as it is taken up by the cells efficiently through endocytosis [34,35]. Colloidal AuNPs incorporating anticancer agents can overcome resistance to drug action, thus reducing the need for higher doses and therefore reducing their ill effects towards normal cells [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…DOX conjugated nanoparticle based drug delivery system evades this mode of efflux as it is taken up by the cells efficiently through endocytosis [34,35]. Colloidal AuNPs incorporating anticancer agents can overcome resistance to drug action, thus reducing the need for higher doses and therefore reducing their ill effects towards normal cells [34,35]. It has been long believed that tumors are acidic in nature through extensive studies using microelectrode measurements [36] or magnetic resonance spectroscopy images [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to create vehicle capable of carrying anticancer drug for targeting therapeutic purposes, we have developed drug loaded baicalein conjugated magnetic nanoparticles and shows efficient drug releasing property (Fig 9). The iron oxide nanoparticles showed a spherical shape as evident from the TEM and SEM analysis and the particle size was about 19nm 21 and doxorubicin coated poly (butylcyanoacrylate) nanoparticles (PBCA NPs) were highly stable spherical particles 22 . The results of our findings too are in accordance with these studies reported.…”
Section: Discussionmentioning
confidence: 96%
“…ABI-007 or NP albumin bound (nab)-paclitaxel has already been approved by the FDA for clinical use90. Zhang et al 91 demonstrated that doxorubicin (DOX) loaded gold NPs, a targeted chemotherapeutic agent, was very effective against a melanoma cell line. However, more studies are needed to streamline the treatment methodologies that can screen out the adverse side effects and only the beneficial effects could be delivered to the patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%